Simulation of Methane Emission from Rice Paddy Fields in Vu Gia-Thu Bồn River Basin of Vietnam Using the DNDC Model: Field Validation and Sensitivity Analysis - Ngô, Đức Minh (ĐHQGHN, 2015)
Irrigated rice cultivation plays an important role in affecting atmospheric greenhouse gas concentrations. In recent years, extrapolation and simulation of impact of farming management on GHGs fluxes from field studies to a regional scale by models approach has been implementing. In this study, the DeNitrification & DeComposition (DNDC) model was validated to enhance its capacity of predicting methane (CH4) emissions from typical irrigated rice-based system in Vu Gia-Thu Bồn River Basin with two water management practices: Continuous Flooding and Alternate Wetting-Drying.2 rice field experiments were conducted at delta lowland (Duy Xuyen district) and midland (Dai Loc district), considered as typical regions along topography transect of study areas. The observed flux data in conjunction with the local climate, soil and management information were utilized to test a process based DNDC model, for its applicability for the rice- based system. The model was further refined to simulate emissions of CH4 under the conditions found in rice paddies of study area. The validated model was tested for its sensitivities to variations in natural conditions including weather and soil properties and management alternatives. The validation and sensitive test results indicated that (1) the modeled results of CH4 emissions showed a fair agreement with observations although minor discrepancies existed across the sites and treatments; (2) temperature factor changes had considerable impact on CH4 emissions; (3) soil properties affected significantly on CH4 emissions; (4) varying management practices could substantially affect CH4 flux from rice paddies. It was suggested that DNDC model is capable of capturing the seasonal patterns as well a